Development of e-Module in Physics Lessons Based on Problem Based Learning - Ngadimin Ngadimin; Pratiwi Jasmine Suwardi; Fitria Herliana; Syamsul Rizal; Musdar Musdar (Asian Journal of Science Education, 2021)
The goal of this study is to develop problem-based learning e-modules that can be used in the teaching and learning process. Research is development research, or RnD (Research and Development), using a 4-D model as a development model (define, design, develop, and dessimate). Students in class X MIPA 2 at SMAN 1 Tangse, a total of 30 participants, were the subjects of this study. These research steps begin with learners receiving a posttest, followed by learners receiving a response questionnaire and posttest questions to determine their level of understanding. After receiving electronics modules, learners are given a response questionnaire and posttest questions to determine their level of understanding. Material and media specialists' validation results fall into the decent and very decent categories, respectively, with percentages of 84.85 and 78.4. The average reaction of learners and teachers is similarly high, indicating that the electronics module is appropriate for use in education. With an average N-Gain value of 0.6, there are 13 people in the high N-Gain category, 15 people in the medium N-Gain category, and 2 people in the low N-Gain category. The N-Gain understanding of learners experiencing an increase in material understanding of momentum and impulses by employing electronics module. Electronics module can be observed in the results.